BIOCELLULOSEAS EDIBLE STRIPS WITHGINGER EXTRACT - Lucia Indrarti; Indriyati Indriyati (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2013)
BIOCELLULOSEAS EDIBLE STRIPS WITHGINGER EXTRACT. The purpose of the studywas to analyze the prospect of biocellulose applied as edible strips, a thin film which can dissolve in the mouth. Edible strips have been prepared by mixing homogenized of biocellulose, Carboxymethyl Cellulose (CMC), glycerol, ginger extract and artificial sweeteners. Then, they were casting and drying. In order to evaluate the effect of the addition of ginger extract on edible strips properties, hedonic test was done with the attributes of color, aroma, taste, and solubility. Crude fiber and water content of edible strips were evaluated as well. The result showed that addition of ginger extract influenced the color, aroma, and taste of edible strips, with the value of 1.9-4, whereas the solubility remained stable at around 2.4-2.6 in 1-5 scale. Variation concentration of ginger extract did not influence the crude fiber and water content of edible strips.Water and crude fiber contents showed 11-14% and 4.5-5.5%, respectively. Temperature at 30 oC and 2 hours of drying of biocellulose composites solution showed the best results to get the optimum of save production cost and energy of edible strips. Based on this result, biocellulose has a prospect to be used as matrix in edible strips.